Luminosity effect of O i 7771–5 triplet and atmospheric microturbulence in evolved A-, F-, and G-type stars. (19th February 2018) - Takeda, Yoichi; Jeong, Gwanghui; Han, Inwoo
Abstract: It is known that the strength of neutral oxygen triplet lines at 7771–5 Å shows a luminosity effect in evolved A through G stars. However, its general behavior across the HR diagram is not yet well understood, since the applicability limit of the relations proposed by various previous work (tending to be biased toward supergiants) still remains unclear. Besides, our understanding on the nature of atmospheric micro-scale turbulence, which is considered to play a significant role (along with the non-LTE line intensification) for the cause of this effect, is still insufficient. Towards clarifying these problems, we carried out an extensive non-LTE spectrum-fitting analysis of O i 7771–5 lines for unbiased sample of 75 evolved A-, F, - and G-type stars over wide luminosity classes (from subgiants through supergiants) including rapid rotators, from which the total equivalent width ( W 77 ) was derived and the microturbulence (ξ) was determined by two different (profile- and abundance-based) methods for each star. While we confirmed that W 77 tends to increase in the global sense as a star's absolute magnitude ( MV ) becomes more luminous, distinctly different trends were found between lower-gravity (log  g ≲ 2.5) and higher-gravity (log  g ≳ 2.5) stars, in the sense that the MV vs. W 77 formulas proposed by past studies are applicable only to the former supergiant group. In case of using W 77 for empirical MV evaluation by such simple formulas, it is recommended to confine only to supergiants of −5 ≳ MV ≳ −10. Regarding the microturbulence significantly controlling W 77, it roughly shows an increasing tendency with a decrease in surface gravity. However, the trend is not monotonic but rather intricate (e.g., hump, stagnation, or discontinuously large increase) depending on the stellar type and evolutionary stage.